Bored, lonely, angry, stupid : changing feelings about technology, from the telegraph to Twitter - Fernandez, Luke; Matt, Susan J. (Susan Jipson), 1967- (London : Harvard University Press, 2019)
Do our digital habits kill our attention span or alter the nature of focus? Is social media driving us apart or changing the meaning of social relationships? How we answer these questions will hinge on what we value. This wide-ranging account of our emotional responses to new technologies, from the telegraph to the smart phone, argues that we are profoundly changed by them. Today, for example, we are increasingly distrustful of social media, yet we have a hard time separating ourselves from the technologies we don't trust. It turns out this is not new: Bored, Lonely, Angry, Stupid reveals how past technological innovations aroused intense feelings and altered our sense of self.--
From vanity to narcissism -- The lonely cloud -- The flight from boredom -- Pay attention -- Awe -- Anger rising.
Includes bibliographical references and index.
Book Aid International 2024 (Donated by the Bhutan Society of the UK Trust Fund)
Keywords: Technology -- Social aspects -- United States; Technology -- United States -- Psychological aspects; Technological innovations -- Social aspects -- United States; Technological innovations -- United States -- Psychological aspects